Optimasi Spesifik-Sifat Pupuk Organik Cair Urine Sapi untuk Bayam Hidroponik Rakit Apung - Sulaminingsih Sulaminingsih; Charlie Novianry Panjaitan; Suwarno Suwarno; M. Rehan Saputra (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Floating raft hydroponics can support rapid leafy vegetable production, yet reliance on commercial mineral nutrient solutions may limit affordability and circularity. This study evaluated the effect of cow urine-based liquid organic fertilizer on the growth of spinach (Amaranthus hybridus L.) in a floating raft hydroponic system and identified the most promising treatment zone. Six coded treatments (B0–B5) were tested with five replications. Plant height, leaf number, and leaf width were measured at 1, 2, and 3 weeks after transplanting, while root length was measured at the final observation. Data were analyzed using one-way ANOVA and eta-squared effect size. The treatments significantly affected all final growth variables. At 3 weeks after transplanting, B2 (35 ml cow urine fertilizer/L water) produced the tallest plants (16.98 ± 0.41 cm), whereas B1 (30 ml cow urine fertilizer/L water) produced the highest leaf number (10.00 ± 1.00 leaves plant−1), the widest leaves (2.60 ± 0.14 cm), and the longest roots (22.68 ± 7.03 cm). Effect sizes were large for final plant height, leaf number, leaf width, and root length. Cow urine-based liquid organic fertilizer markedly shaped spinach vegetative growth, but the response was non-linear. B1–B2 represent the most promising treatment zone.